Determination of critical power in swimming - Kokubun, E.; Pessoa-Filho, D. M.; Sibuya, C. Y. (Medicine & Science in Sports & Exercise, 1999)
Critical velocity (CV) is proposed as a good estimator of anaerobic threshold in swimming. Originally, critical power assumed a hyperbolic relationship with power output, not velocity, and time to exhaustion. This study investigated: i) the actual critical power in swimming using a work-time model, and ii) the prediction of swimming performance using the work-time and distance-time models. Swimmers performed 50, 100, and 200-m maximum efforts and their anaerobic thresholds (AT, 4 mM fixed-blood lactate concentration velocity) were determined. Critical power and anaerobic work capacity were determined using the 100 and 200-m power outputs. Anaerobic work capacity accounted for the greatest amount of variance in the shortest distance swim while critical power was related more to the longest swim. It was concluded that critical power can be calculated in swimming and that it is a better predictor of short sprint performances than velocity based models. Implication: Critical power is a better predictor of short sprint performances than is velocity. One has to ask though, why not just sprint 50 m as fast as possible and use that as the time of interest instead of going to some long drawn-out procedure to get a partial estimate of that which can be so easily obtained?